Pride, faith, and fear: Islam in Sub-Saharan Africa - Quinn, Charlotte A. (Oxford University Press, 2003)
While nearly one in every five people in the world today is Muslim, Islam is spreading most rapidly in Sub-Saharan Africa which is today home to over 150 million Muslims. Although immensely varied, African Islam, the authors demonstrate, is defined by three overarching beliefs.